2007
DOI: 10.1097/01.anes.0000290588.29668.38
|View full text |Cite|
|
Sign up to set email alerts
|

Predictors of Postoperative Acute Renal Failure after Noncardiac Surgery in Patients with Previously Normal Renal Function

Abstract: Background: The authors investigated the incidence and risk factors for postoperative acute renal failure after major noncardiac surgery among patients with previously normal renal function.Methods: Adult patients undergoing major noncardiac surgery with a preoperative calculated creatinine clearance of 80 ml/min or greater were included in a prospective, observational study at a single tertiary care university hospital. Patients were followed for the development of acute renal failure (defined as a calculated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
310
10
15

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 459 publications
(363 citation statements)
references
References 34 publications
28
310
10
15
Order By: Relevance
“…19 The RIFLE criteria 19 and subsequent AKIN definition 11 have addressed this methodological deficiency. Acute kidney injury following cardiac, vascular surgery, and major noncardiac surgery has been well studied; 5,16,[20][21][22][23] however, AKI following joint arthroplasty has received less attention. 6,7,24 Though our study was not designed to determine the incidence of postoperative AKI, the percentage of cases (1.8%) that experienced postoperative AKI is higher than previous estimates (0.4-0.55%), likely reflecting increased sensitivity of our modified AKIN criteria compared with RIFLE criteria, 11,19 which may introduce an ascertainment bias.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 The RIFLE criteria 19 and subsequent AKIN definition 11 have addressed this methodological deficiency. Acute kidney injury following cardiac, vascular surgery, and major noncardiac surgery has been well studied; 5,16,[20][21][22][23] however, AKI following joint arthroplasty has received less attention. 6,7,24 Though our study was not designed to determine the incidence of postoperative AKI, the percentage of cases (1.8%) that experienced postoperative AKI is higher than previous estimates (0.4-0.55%), likely reflecting increased sensitivity of our modified AKIN criteria compared with RIFLE criteria, 11,19 which may introduce an ascertainment bias.…”
Section: Discussionmentioning
confidence: 99%
“…At present, most studies that have tried to define these factors have examined heterogenous surgical populations. 5 In contrast, AKI following joint arthroplasty has not been well characterized, and to date, few studies on this topic have been published. 6,7 The primary aim of the present study is to undertake further exploration of the preoperative and intraoperative factors associated with postoperative AKI in patients undergoing total joint arthroplasty.…”
mentioning
confidence: 99%
“…38 Urine output is also frequently monitored as a crude marker of renal function and volume status; yet, in the perioperative period, oliguria (defined as UOP \ 0.5 mLÁkg -1 Áhr -1 ) is extremely common and often occurs as a neurohormonal response to surgical stress, rendering it an unreliable marker of volume status. 39 Goal-directed fluid therapy Goal-directed fluid therapy (GDFT) utilizes a cardiac output monitor to individualize fluid therapy. The technique is also referred to in the literature as stroke volume (SV) optimization, as the goal is to optimize the patient's SV throughout the perioperative period.…”
Section: Maintenance Fluid Therapymentioning
confidence: 99%
“…39 There are other mechanisms that may cause low UOP, including intraoperative releases of stress hormones. Hahn showed that the clearance of fluids during general anesthesia is only a small fraction of that observed when awake.…”
Section: Low Perioperative Uopmentioning
confidence: 99%
“…The study findings are relevant not only because of the presence of patients with preexisting renal insufficiency or hepatic impairment in surgical populations, but also in light of the transient renal insufficiency that can occur as a result of altered hemodynamics (which can affect renal perfusion) during major (eg, intrathoracic, intraperitoneal) surgical procedures 39, 40. The results of this study therefore provide a first indication that HPβCD‐diclofenac may be administered to patients with mild or moderate renal insufficiency or mild hepatic impairment at the usual dose and schedule without a need for dose reduction.…”
Section: Discussionmentioning
confidence: 99%